PENGEMBANGAN BUKU AJAR MATEMATIKA KURIKULUM MERDEKA UNTUK SISWA KELAS I SEKOLAH DASAR - Hengkang Bara Saputro (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2024)
The development of mathematics textbooks is motivated by the limited ability and willingness of teachers to develop innovative teaching materials that suit the characteristics of grade I elementary school students in the Independent Curriculum. Therefore, through this research, it is hoped that we will be able to develop a mathematics textbook that can be used as independent teaching material for students which can improve student learning outcomes in mathematics subjects which are still considered difficult by some students. The aim of this research is to develop a grade I elementary school mathematics textbook using the Independent Curriculum and to determine the feasibility and practicality of the book being developed. This research uses Research and Development (RnD) research. The development model used to develop teaching material products in the form of textbooks refers to the steps in developing design research of the development study type, namely: (1) Preliminary research, (2) Prototyping stage, (3) Summative evaluation, and (4) Systematic reflection and documentation. The data collection instrument consists of a validation sheet and a questionnaire sheet. Validation sheet to determine the suitability of the product from the assessment of media experts, material experts and learning experts. Questionnaire sheet to find out teacher and student responses. The results obtained from this research showed that the feasibility of the research was seen from the validation aspect of media experts, namely 87 in the "very good" category, material experts 82.85 in the "very good" category, learning experts 86 in the "very good" category, then for teacher responses obtained a result of 96.67 in the "very practical" category and students obtained a response result of 94.23 in the "very practical" category. Based on these results, the mathematics textbook that has been developed for grade I elementary school students is very suitable for use.